2020
DOI: 10.1002/ijgo.13409
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous shortage of blood banks as an indirect effect of SARS‐CoV‐2: An obstetrics perspective

Abstract: Objective: To describe the impact of the SARS-CoV-2 pandemic on the frequency of blood donation (BD) in a Latin American hospital and how the social isolation policy implemented during the pandemic jeopardizes the quality of postpartum hemorrhage (PPH) care due to shortages at blood banks (BB). Methods: A retrospective, descriptive study was conducted, lasting for 31 months, including the start of the pandemic. Frequency of BD and the use of obstetric emergency services was observed. Results: A direct relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…The scenario seems to be expected, especially in the resource-limiting countries where COVID-19 testing is very costly and not affordable by the general population in the early and mid-phase of the pandemic. That has resulted in the scarcity of the blood supply in the blood banks, which has primarily affected many aspects of medical surgery, emergency, and regular treatments requiring blood, such as in thalassemia [4]. Moreover, blood transfusion is routinely needed in medical procedures to replace blood losses during surgery, injury, obstetrics and other operations as a life-saving option.…”
Section: Blood Scarcity During Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…The scenario seems to be expected, especially in the resource-limiting countries where COVID-19 testing is very costly and not affordable by the general population in the early and mid-phase of the pandemic. That has resulted in the scarcity of the blood supply in the blood banks, which has primarily affected many aspects of medical surgery, emergency, and regular treatments requiring blood, such as in thalassemia [4]. Moreover, blood transfusion is routinely needed in medical procedures to replace blood losses during surgery, injury, obstetrics and other operations as a life-saving option.…”
Section: Blood Scarcity During Covid-19 Pandemicmentioning
confidence: 99%
“…They have not been restarted yet in many places. Even though some campaigns have been conducted for blood donation while adopting the appropriate safety measures, very few people came forward for blood donation during the pandemic, affecting blood supply and use and posing significant implications for blood transfusion [2][3][4][5][6]. Furthermore, it has recently been discovered in the United States that the COVID-19 pandemic has resulted in severe blood scarcity for medical transfusions, aggravating an already precarious blood supply system, which in turn causes public health issues and raises new issues about emergency preparedness plans for assuring blood supplies [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is a widespread shortage of blood supply and demand in many parts of the world, significantly affecting blood transfusion services. [1][2][3][4][5][6][7] The blood donation process was negatively influenced by the COVID-19 pandemic due to a dramatic decrease in blood donors, forcing blood banks and blood donation centers to implement new policies to increase blood supply while protecting donors from COVID-19 infection. 8…”
Section: Introductionmentioning
confidence: 99%
“…Many countries responded to concerns about the impact of the pandemic on blood supplies by implementing measures to reduce the demand for blood, such as cancelling elective surgery (Stanworth et al, 2020), while BCAs issued call outs for donors (Mohammadi et al, 2020). Studies have reported that these measures successfully mitigated shortages in the short-term, however the problem of maintaining the blood supply in these unprecedented circumstances is a long-term one, given the longevity and unique features of this pandemic, and ongoing demand for blood for procedures that require transfusion (Nieto-Calvache et al, 2020). During previous national crises, such as 9/11 in the United States and bushfires in Australia, donors and non-donors have been shown to respond positively to calls to donate blood (Glynn et al, 2003, Spekman et al, 2021, Tran et al, 2010.…”
Section: Introductionmentioning
confidence: 99%